PENERAPAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE (MDLC) DALAM PEMBUATAN APLIKASI MOBILE EDUKASI LINGKUNGAN “CINTA MANGROVE” - Hermansyah, Hermansyah; Wijaya, Rian Farta; Wahyuni, Sri; Putra, Agil Dwi (Smart Education, 2024)
Abstract: The degradation of mangrove ecosystems in coastal areas has become an increasingly concerning environmental issue, partly due to the lack of public knowledge and awareness regarding the importance of mangrove conservation. This study aims to develop a mobile environmental education application entitled “Cinta Mangrove” by applying the Multimedia Development Life Cycle (MDLC) method. The MDLC method consists of six stages: concept, design, material collection, assembly, testing, and distribution. In the evaluation stage, testing was conducted using pre-tests and post-tests to measure the improvement in users’ knowledge before and after using the application. Beta testing was carried out by comparing pre-test and post-test results through questionnaires. The results showed an increase in participants’ average understanding from 60% before using the application to 85% after its use. The findings indicate a significant improvement in participants' comprehension of the functions and importance of mangrove preservation. The